Physical and chemical properties of heartwood and sapwood of Cryptomeria japonica (Revista de Ciências Agroveterinárias, 2017)
The study of the physical properties and chemical composition of the wood are of great importance for being related to industrial transformation as well as its aptness the most varied forms of use. On this basis, this study aimed to evaluate the chemical and physical properties of Cryptomeria japonica in wood samples for the heartwood and sapwood. The chemical properties of the content of extractives, lignin and inorganic materials content and hydrogenic potential (pH) were determined. The physical properties related to determination of density and dimensional stability, were evaluated by using 951 samples. In general, both wood samples presented chemical properties compatible with the literature for Cryptomeria japonica. For both samples a low content of extractives was obtained, being lower in the sapwood. The results indicated that the species presented density from low to medium; it is similar to both wood samples. Regarding the dimensional stability Cryptomeria japonica was rated as good stability.
Keywords: wood density; dimensional stability; extractives.